What are the experiences of therapists using the online Back Skills Training and implementing it within clinical practice? - Christou, B; Sellars, J; Barker, K (Wiley, 2019)
Introduction: The purpose of the present study was to explore the experiences of physiotherapists using the online Back Skills Training (i‐BeST). The aim of the this programme was to enable clinicians to facilitate group‐based treatment based on a cognitive behavioural (CB) approach to the treatment of lower back pain (LBP).